UPAYA MENINGKATKAN PEMAHAMAN KONSEP SOSIOLOGI SISWA DENGAN MENGGUNAKAN KETERAMPILAN BERVARIASI GURU DI KELAS X IPS SMA NEGERI 1 LEMBAH MELINTANG - Maisaroh Maisaroh Maisaroh (Horizon, 2021)
Learning is never free from problems that can appear at any time and become an obstacle to achieving learning goals. One of these problems is the difficulty of students in understanding the concept of sociology lessons because teachers have not been optimal in improving students' understanding of concepts. This can be seen in SMA Negeri 1 Lembah Melintang that it is found that there are still many students who do not understand the learning material on the subject of Sociology properly. The theory used is the Cognitive Exchange Theory proposed by Ritzer. The research was conducted at group X IPS 3 SMAN 1 Lembah Melintang. This classroom action research was carried out in 2 cycles with 4 stages, namely planning, implementing, observing and reflecting. Data analysis was carried out by looking at students 'individual completeness and classical completeness to see the understanding of students' sociological concepts. The results of this study indicate that by using varied skills teachers can improve the understanding of the concept of sociology of class X IPS 3 SMAN 1 Lembah Melintang. In, in cycle I, the average learning outcomes to see the understanding of students 'sociological concepts was 71.67 with a completeness percentage of 27.78% and increased in cycle II, namely the average learning outcomes to see students' understanding of sociological concepts became 78.89 with a completeness percentage of 86.11% because in cycle II students' understanding of the concept of sociology has increased, marked by learning outcomes that have reached the KKM